The results of monitoring the properties of road embankment soils - Vynnykov, Yuriy; Ilchenko, Volodymyr; Yermolenko, Dmytro; Lvovska Тetiana (Academic journal. Industrial Machine, Building Civil Engineering, 2022)
For five full-scale objects, research methodology and geotechnical control results of physical and mechanical characteristics of in layers compacted silty loam within the road embankment after its construction and before the operation start are presented. According to the statistical analysis of the two-factor experiment data sample, empirical coefficients values of the analytical dependence of stabilized moisture for loams’ in layers rolling on the value of soil skeleton density within the embankment and the plasticity index of these soils were obtained. It has been proven that this parameter corresponds to the maximum molecular moisture capacity in clay soils, at which it is most expedient to do in layers compaction to ensure subgrade long-term strength